2008
DOI: 10.1016/j.bbrc.2008.02.126
|View full text |Cite
|
Sign up to set email alerts
|

Role of AMP-activated protein kinase in autophagy and proteasome function

Abstract: In this work, we have examined the possible role of AMP-activated protein kinase (a key energy sensor) in regulating intracellular protein degradation. We have found that AICAR, a known activator of AMPK, has a dual effect. On one hand, it inhibits autophagy by a mechanism independent of AMPK activity; AICAR decreases class III PI3-kinase binding to beclin-1 and this effect counteracts and reverses the known positive effect of AMPK activity on autophagy. On the other hand, AICAR inhibits the proteasomal degrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 27 publications
6
50
0
Order By: Relevance
“…A recent study with mouse and human endothelial cell cultures has demonstrated that AMPKα2 can modestly reduce proteasome activity; this likewise results in a downregulation of NF-kappaB activation . (A similar effect of AMPK on proteasomes has been reported in fibroblasts (Viana et al 2008).) This downregulation of NF-kappaB, in turn, results in decreased expression of various components of the NAPDH oxidase complex .…”
Section: Vascular Protectionsupporting
confidence: 74%
“…A recent study with mouse and human endothelial cell cultures has demonstrated that AMPKα2 can modestly reduce proteasome activity; this likewise results in a downregulation of NF-kappaB activation . (A similar effect of AMPK on proteasomes has been reported in fibroblasts (Viana et al 2008).) This downregulation of NF-kappaB, in turn, results in decreased expression of various components of the NAPDH oxidase complex .…”
Section: Vascular Protectionsupporting
confidence: 74%
“…Activation has been shown to stimulate catabolism and inhibit fatty acid and cholesterol synthesis, with the net effect of reducing ATP consumption and promoting anaerobic ATP synthesis (21). AMPK activation has also been implicated in promoting cell survival by regulating macroautophagy (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…37 Moreover, it was shown that AMPK suppresses proteasome-dependent proteolysis in vitro. 22 Xu et al reported that proteasome-dependent degradation of GTPCH I was related to endothelial dysfunction in diabetes. 19 Wang et al reported that the inhibition of GTPCH I degradation by AMPK activation attenuated endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent reports indicate that AMP-activated protein kinase (AMPK) suppresses proteasome-dependent protein degradation in vitro. 22 Moreover, some reports show that proteasome-dependent GTPCH I degradation is key for diabetesinduced endothelial dysfunction. 19,23 Therefore, we also investigated whether metformin, an oral hypoglycemic agent and AMPK activator, exerts a protective effect in diabetic nephropathy.…”
mentioning
confidence: 99%